Tugging at hairstrings hair embroidery as a metaphor for adoption - Conanan, Sarah Mae M.; Concepcion, Reynaldo L. (Quezon City College of Fine Arts, University of the Philippines Diliman, 2019)
Family is the core group that helps identify and mould a person. Unfamiliarity with the concept of or the physical absence of the family can cause an individual to experience a feeling of incompleteness. The proponent confronts this feeling of incompleteness and uncertainty brought about by the knowledge of her adoption from birth.

This thesis aims to create a visual articulation of the proponent's search for a biological family embodied in a question that constantly demands to be answered despite the proponent having no means to do so while settled within a family that has raised her as its own. Hair as a visual metaphor for these concerns is integral to achieving the objectives of the thesis and the creation of the thesis works. The chosen process for this thesis is embroidery and manipulation of hair as an alternative material for thread.
Thesis (Bachelor of Fine Arts in Painting)--University of the Philippines Diliman
Bibliography: leaves 28-29
Keywords: Adoption; Parent and child; Hair; Family